Assessing gender gaps among women street vendors and hawkers: A study of women as stakeholders of agri-food systems of India - Sailaja Bharatam, Sal; Nambiar, Sridip S.; Kumar, Abhijeet (Narsee Monjee Institute of Management Studies, India, 2023)
Agency will (government support) plays a crucial role in achieving palpable results toward gender justice through empowerment. Women street hawkers and vendors selling greens, flowers, meat and fish in urban and rural areas take a vital place in the agri-food systems. These small day-to-day businesswomen play a major role in bringing in the produce to markets for sale. Understanding their impact on the ecosystem of the respective supply chains will enable future research on the positioning and impact of these vendors and hawkers in the ecosystem. In our work, we sought to understand three aspects of women street vendors and hawkers: (a) The time invested and the gains they receive on a day-to-day basis. What is their present status of technology usage in terms of phones, smart phones, and digital payments? What are the pros and cons of digital transformation in their lives? What aspirations they hold for the future and upgrade of technological help for further improvement to their lives? (b) What alternatives are available and what are the opportunity costs involved if they are moving out of their routine? What is their awareness of saving and support systems they have for a rainy day? (c) What is their awareness of and aspirations for governmental intervention in their lives? The work will collect 20 plus personal interviews of both men and women street vendors and hawkers through a survey from a metropolitan, semi-urban and rural areas of Telanagana and Andhra Pradesh. The present work will facilitate and help understand the agency that is the government for a relevant intervention and support for the betterment of the women street vendors and hawkers.